2003
DOI: 10.1385/ni:1:1:043
|View full text |Cite
|
Sign up to set email alerts
|

NeuroNames 2002

Abstract: NeuroNames is a nomenclature designed as a tool for indexing digital databases of neuroscientific information. It can be used, for example, as the entry point to a digital dictionary of neuroanatomy, to a brain atlas, or to a database of information referenced to specific brain structures. The user can query with terms from many different nomenclatures. One can create a neuroanatomic ontology from NeuroNames by relating an appropriate subset of terms to a conceptual model represented by structures illustrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 4 publications
0
67
0
1
Order By: Relevance
“…For each publication indexed, the reported groups and individuals are characterized with respect to the demographic, clinical and anatomic measurements reported. To facilitate interdatabase federation, many elements of the database are related to 'concept' entries in the Unified Medical Language System (UMLS) [Hole & Srinivasan, 2003] including the anatomic nomenclature (through NeuroNames [Bowden and Martin, 1995;Bowden and Dubach, 2003]] and diagnosis codes (DSM-4 and ICD-10).…”
Section: Methodsmentioning
confidence: 99%
“…For each publication indexed, the reported groups and individuals are characterized with respect to the demographic, clinical and anatomic measurements reported. To facilitate interdatabase federation, many elements of the database are related to 'concept' entries in the Unified Medical Language System (UMLS) [Hole & Srinivasan, 2003] including the anatomic nomenclature (through NeuroNames [Bowden and Martin, 1995;Bowden and Dubach, 2003]] and diagnosis codes (DSM-4 and ICD-10).…”
Section: Methodsmentioning
confidence: 99%
“…The UMLS has recently incorporated the NeuroNames ontology 53 as a source vocabulary. NeuroNames is a comprehensive resource for gross brain anatomy in the primate.…”
Section: A Case Study: the Cell Centered Database 45mentioning
confidence: 99%
“…One important use is to facilitate an understanding of what design properties of an intracellular network are necessary for its function. For example, von Dassow et al 53 used a simulation model of the gap and pair-rule gene network in Drosophila melanogaster to show that the structure of the network is sufficient to explain a great deal of the observed cellular patterning. In addition, they showed that the network behavior was robust to parameter variation upon the addition of hypothetical (but reasonable) elements to the known network.…”
Section: On Inferring Qualitative Connectionsmentioning
confidence: 99%
See 2 more Smart Citations